Odpowiedzi

Najlepsza Odpowiedź!
2009-11-22T19:08:04+01:00
A2 = 2
a6 = 14
---------------
a9 = ?

a2 = a1 +r
a6 = a1 +5r, czyli
a1 + r =2 --------> a1 =2 -r
a1 + 5r = 14
(2 -r) +5r = 14
4r = 14 -2 = 12
r = 12 :4 = 3
a1 = 2-r = 2 - 3 = -1
Mamy a1 = -1 oraz r = 3
a9 = a1 +(9 -1)*r =-1 +8*3 = 24 - 1 =23
Odp. a9 = 23
6 4 6
2009-11-22T19:12:48+01:00
A2=2
a6=14
an=a1+(n-1)r

a2=a1+r
a6=a1+5r

2=a1+r
14=a1+5r

a1=2-r
14=2-r+5r

a1=2-r
14-2=4r

a1=2-r
4r=12 /:4

a1=2-r
r=3

a1=2-3=-1

a9=a1+8r
a9=(-1) + 8*3=-1+24=23

Odp. Dziewiąty wyraz ciągu wynosi 23
3 5 3